2015
DOI: 10.1080/00918369.2015.1078203
|View full text |Cite
|
Sign up to set email alerts
|

“We Don’t Get Into All That”: An Analysis of How Teachers Uphold Heteronormative Sex and Relationship Education

Abstract: Abstract:In light of literature that highlights the heteronormative nature of secondary school Sex and Relationship Education (SRE) (Ellis & High, 2004;Stonewall, 2007); this study examines how teachers account for their provision as inclusive of young people's sexual diversities. These accounts construct young LGB people and those who engage in same-sex sexual practices as isolated cases and therefore outside of the remit of mainstream SRE provision. The strategies used involve problematising samesex sexualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…The accepted constructions of sexuality tend to privilege heterosexual, monogamous relationships whose sexual practice is predominantly genitally and reproductively based (Shildrick, 2007). Further, those who work with, or are close to autistic people, such as teachers, are themselves products of an educational system in which LGBTQ and autistic sexuality, if discussed at all, is treated as if these were isolated cases, 'reinforcing the presumption of heterosexuality, problematizing same-sex sexuality …' (Abbott, Ellis, & Abbott, 2015:1653. Since many autists transgress the sociocultural norms of sexuality (Maeve and Lilly Snowball do) their sex lives are often viewed through a lens of disgust (Shakespeare, 1996).…”
Section: Redressing Epistemic Injustice: the Need For Sex And Sexualimentioning
confidence: 99%
“…The accepted constructions of sexuality tend to privilege heterosexual, monogamous relationships whose sexual practice is predominantly genitally and reproductively based (Shildrick, 2007). Further, those who work with, or are close to autistic people, such as teachers, are themselves products of an educational system in which LGBTQ and autistic sexuality, if discussed at all, is treated as if these were isolated cases, 'reinforcing the presumption of heterosexuality, problematizing same-sex sexuality …' (Abbott, Ellis, & Abbott, 2015:1653. Since many autists transgress the sociocultural norms of sexuality (Maeve and Lilly Snowball do) their sex lives are often viewed through a lens of disgust (Shakespeare, 1996).…”
Section: Redressing Epistemic Injustice: the Need For Sex And Sexualimentioning
confidence: 99%
“…While critiques of the heteronormativity of sexuality education and the need for the inclusion of sexuality diversity has been noted for some time (e.g. Abbott, Ellis, and Abbott 2015;Buston and Hart 2001;Elia and Eliason 2010;McNeill 2013), very little has been written about sexuality education in relation to transgender people. Riggs (2013) has noted, for example, the ways in which sexuality education websites drawn on by schools typically only refer to people who are gay or lesbian, and ignore those who may be bisexual, transgender, intersex, or queer.…”
Section: Sexuality Educationmentioning
confidence: 99%
“…As a contribution to such a goal, the present study aims to expand on previous research highlighting how teachers' discourse, and the assumptions underpinning it, influences the nature and scope of SRE (Abbott, Ellis, and Abbott 2015). As opposed to a sole focus on heteronormativity, the present study examines how a variety of assumptions and discourses underpin teachers' justifications of sexual health provision in the context of non-statutory guidance.…”
Section: Introductionmentioning
confidence: 98%
“…This type of provision ultimately serves the interests of conservative interest groups rather than young people themselves (Abbott, Ellis, and Abbott 2015). More importantly, while the teachers delivering the content may be influential in the formation of young people's future identities (Mayo 2013), research has shown that they face a number of barriers in the delivery of SRE (Atkinson 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation